Combinatorial cell-3D biomaterials cytocompatibility screening for tissue engineering using bioinspired superhydrophobic substrates - Salgado, Christiane L. (2012)
We report on the development of a new array-based screening flat platform with the potential to be used as a high-throughput device based on biomimetic polymeric substrates for combinatorial cell/3D biomaterials screening assays in the context of tissue engineering. Polystyrene was used to produce superhydrophobic surfaces based on the so-called lotus effect. Arrays of hydrophilic regions could be patterned in such surfaces using UV/ozone radiation, generating devices onto which combinatorial hydrogel spots were deposited. The biological performance of encapsulated cells in hydrogels could be tested in an in vitro 3D environment assuming that each site was isolated from the others due to the high contrast of wettability between the patterned spots and the superhydrophobic surroundings. Three different polymers-chitosan, collagen and hyaluronic acid-were combined with alginate in different proportions in order to obtain combinatorial binary alginate-based polymeric arrays. The effect of the addition of gelatin to the binary structures was also tested. The gels were chemically analyzed by FTIR microscopic mapping. Cell culture results varied according to the hydrogel composition and encapsulated cell types (L929 fibroblast cells and MC3T3-E1 pre-osteoblast cells). Cell viability and number could be assessed by conventional methods, such as MTS reduction test and dsDNA quantification. Non-destructive image analysis was performed using cytoskeleton and nuclei staining agents and the results were consistent with the ones obtained by conventional sample-destructive techniques. Briefly, L929 cells showed higher number and viability for higher alginate-content and collagen-containing hydrogels, while MC3T3-E1 showed higher cell viability and cell number in lower alginate-content and chitosan containing hydrogels. The addition of gelatin did not influence significantly cell metabolic activity or cell number in any of the encapsulated cell types.